Penerapan Flipped Classroom dalam Peningkatan Hasil Belajar Ikatan Kimia pada Kuliah Kimia Dasar - Stefan Marco Rumengan; Jakub Saddam Akbar; Yana Sambeka; Vlagia Paat (Oxygenius: Journal Of Chemistry Education, 2023)
Flipped classroom is a learning approach where subject matter and skills that are usually taught during class hours are delivered outside the classroom. This research aims to determine differences in student learning outcomes through the application of the flipped classroom learning model on basic chemistry material in mathematics education at Universitas Negeri Manado (Unima). This research is quantitative research using experimental methods with a one-group pretest-posttest design. The sample used in this research was class A mathematics education students with a low or no level of understanding of chemistry. The data collection technique uses a learning outcomes test where a pretest is given before the lecture process is carried out and a posttest after the lecture process is carried out. The research results showed that the average student learning outcomes in the pre-test were 37.71 and the average student learning outcomes in the post-test were 87.88. The N-Gain score test results show a score of 81% which is included in the effective and high category. Based on these results, it can be concluded that the application of the flipped classroom model improves student learning outcomes in chemical bond material in the general chemistry class at Unima’s mathematics education effectively and significantly.